2009
DOI: 10.1159/000217798
|View full text |Cite
|
Sign up to set email alerts
|

Results of Reconstruction with Jejunal Pouch after Gastrectomy: Correlation with Gastrointestinal Motor Activity

Abstract: Background/Aims: To investigate if restoration of esophago-intestinal or esophago-gastric continuity with a jejunal pouch after total or proximal gastrectomy has clinical benefits. Methods: We reviewed all relevant reports published after 1990 that dealt with the clinical results of reconstruction with a jejunal pouch after total and proximal gastrectomies and correlated those findings with results for gastrointestinal motility. Reports were chosen from a search of the literature using PubMed. Results: After t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 64 publications
1
14
0
1
Order By: Relevance
“…In addition, postoperatively, the formation of a pouch seems to be beneficial with regard to oral nutrient intake and weight gain, as weight loss in the pouch groups was significantly less than in the simple Roux-en-Y reconstruction group, which is consistent with other studies demonstrating better postoperative food intake and weight gain [11,12]. As pouch formation results in the reservoir function and decelerates food passage, this allows a more physiological digestion and absorption [13,14]. The additional jejunoplasty did not show a significant additional benefit.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, postoperatively, the formation of a pouch seems to be beneficial with regard to oral nutrient intake and weight gain, as weight loss in the pouch groups was significantly less than in the simple Roux-en-Y reconstruction group, which is consistent with other studies demonstrating better postoperative food intake and weight gain [11,12]. As pouch formation results in the reservoir function and decelerates food passage, this allows a more physiological digestion and absorption [13,14]. The additional jejunoplasty did not show a significant additional benefit.…”
Section: Discussionsupporting
confidence: 86%
“…Esophagogastrostomy is the fastest and simplest method, however it is also known to cause severe gastroesophageal reflux in some patients. Some authors interpose a segment of the small bowel as a reservoir in a single row type or in a pouch type and reported that these interposition methods seemed to produce less reflux [21,22,23,24,25,26,27]. However, some unexpected serious complications by dilatation of the pouch were also noticed in the interposition methods [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Some reports supported the advantage of pouch reconstruction after total gastrectomy [17][18][19][20]. For example, Shibata et al [21] reported in their review article that six reports where pouch RY reconstruction was used showed improvements in body weight, QOL, eating capacity, and reflux symptoms compared to RY reconstruction without a pouch, while three reports showed no difference.…”
Section: Total Gastrectomymentioning
confidence: 99%